Seroprevelance of Dengue Among Healthy Blood Donors in Blood bank - Sapkota, Jyotshna; Thapa, Ranjan; Nepal, Basudha; Adhikari, Ram Prasad; Khadka, Sushila; Aryal, Kiran; Acharya, Avinav; Kunwar, Saroj; Khanal, Laxmi Kant (Journal of Nepal Health Research Council, 2024)
Background: Dengue is a viral infection, commonly found in tropical and subtropical regions across the globe particularly in urban and semi-urban settings. There has been significant increase in dengue cases over past two decades. This study aims to determine the prevalence of dengue NS1 antigen, IgM, and IgG antibodies among healthy blood donors at the Nepal Medical College Blood Bank. Methods: The descriptive cross-sectional study was carried out at the blood bank of Nepal Medical College between August to November 2023. Ethical approval was received from the Institutional Review Committee of Nepal Medical College (Ref: -080/081). Two hundred and thirty two serum samples from the healthy blood donors were screened with Dengue RDT (SD Bioline Dengue Duo) for detection of NS1 antigen, IgM and Ig G antibodies. Results: Among the samples 18/232 (7.75%) were found IgM positive and 25/232 (10.77%) were found IgG positive. Similarly, 12/232 (5.17%) showed both IgG and IgM positive; however, all sample tested negative for NS1 Conclusions: Detection of Dengue antibodies in asymptomatic blood donors in endemic areas indicates a potential risk for recipients to contract dengue infection through blood transfusion. Implementing a screening program during dengue outbreaks could effectively mitigate this risk. Keywords: Blood donors; dengue; seroprevalence.